2016
DOI: 10.1111/1462-2920.13259
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions of archaea, bacteria and viruses in a hypersaline endolithic community

Abstract: Halite endoliths in the Atacama Desert represent one of the most extreme ecosystems on Earth. Cultivation-independent methods were used to examine the functional adaptations of the microbial consortia inhabiting halite nodules. The community was dominated by haloarchaea and functional analysis attributed most of the autotrophic CO2 fixation to one unique cyanobacterium. The assembled 1.1 Mbp genome of a novel nanohaloarchaeon, Candidatus Nanopetramus SG9, revealed a photoheterotrophic life style and a low medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 79 publications
(137 reference statements)
9
139
3
Order By: Relevance
“…Only one archaeal OTU was detected in our data at very low abundance (0.007%) and was filtered out from our quality‐controlled dataset because of potential sequencing errors. This absence of archaeal lineages is interesting – but not surprising – as previous work on lithic microbial communities have also reported the absence or extremely low abundance, of archaea in these habitats (Pointing et al ., ; DiRuggiero et al ., ), with the exception of endolithic halite communities (Crits‐Christoph et al ., ; Finstad et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one archaeal OTU was detected in our data at very low abundance (0.007%) and was filtered out from our quality‐controlled dataset because of potential sequencing errors. This absence of archaeal lineages is interesting – but not surprising – as previous work on lithic microbial communities have also reported the absence or extremely low abundance, of archaea in these habitats (Pointing et al ., ; DiRuggiero et al ., ), with the exception of endolithic halite communities (Crits‐Christoph et al ., ; Finstad et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, because of high atmospheric deposition of nitrate in parts of the Atacama Desert (Friedmann and Kibler, ; Michalski et al ., ), it has been suggested that nitrate could be a source of nitrogen for the communities. This was supported by the absence of nitrogen fixation genes in metagenomes from several endolithic communities from the Atacama Desert (Crits‐Christoph et al ., ; Finstad et al ., ). While we were not able to measure soluble iron for these substrates (because of limited amount of substrate), iron limitation would be consistent with the enrichment of genes for iron acquisition and siderophores previously described for ignimbrite and calcite substrates collected in the Atacama Desert (Crits‐Christoph et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with increasing evidence pointing out to the presence of briny liquid water on present-day Mars 4 these space analogues became key ecosystems for understanding the adaptability of life (as we know it) at low water activity and for seeking potential microbial biosignature markers 5 . Despite the fact that recent studies on saline meromictic lakes 6 and halite endoliths 7 broadened our current view on microbial diversity and adaptability to the high-salt milieu, most of our current understanding of hypersaline environments is derived from studies performed on solar salterns, sabkhas or saline lakes. Although sapropels 8 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are (1) differential RNA-sequencing (dRNA-seq) and (2) size-selected, strand-specific sRNA-sequencing (sRNA-seq) [14,32]. Both methods preserve the strand-specificity that has been key to the identification of antisense sRNAs in Archaea.…”
Section: Best Methods For Srna Discoverymentioning
confidence: 99%